Gestão de ativos e passivos nas instituições financeiras do mercado brasileiro: uma abordagem na alocação de capital - Marques Filho, Drauzio Ferreira (2008)
The present paper aims to present an implementation proposal of a structured process for assets and liabilities management. This process main purpose is the shareholder s capital profitability optimization, guaranteeing not only controlled and qualified risks but also that the fair capital cost is paid by the ones who use it. The capital quantification basis was made according to Basiléia II precepts, comprising Loan, Market and Operational risk, from the regulation part view, as well as from the proprietary models view, which possibly is going to be adopted in 2012 when these controls implementation should be finished. Thus, other effects that may affect an operation cost were comprised, such as direct and indirect taxes. To better contextualize this paper and demonstrate the process importance, a brief Brazilian financial system evolution and description has been made